Applications of Feket-Szeg¨o Inequalities for Generalized Sakaguchi Type Functions to Fractional Derivative Operator (MATEMATIKA, 2014)
In the present paper, we have given the applications of Feket-Szeg¨ o in- equalities for generalized Sakaguchi type functions obtained recently by us. We have investigated Feket-Szeg¨ o inequalities of certain classes of functions deﬁned through fractional derivatives. The applications of Feket-Szeg¨ o inequalities for subclass of func- tions deﬁned by convolution with a normalized analytic functions are also given. Keywords : Sakaguchi functions; Subordination; Fekete-Szeg¨ o inequality; Convolution 2010 Mathematics Subject Classiﬁcation 30C45; 30C50; 30C80